Bidirectional Contrast agent leakage correction of dynamic susceptibility contrast (DSC)‐MRI improves cerebral blood volume estimation and survival prediction in recurrent glioblastoma treated with bevacizumab. Issue 5 (12th March 2016) - Leu, Kevin; Boxerman, Jerrold L.; Lai, Albert; Nghiemphu, Phioanh L.; Pope, Whitney B.; Cloughesy, Timothy F.; Ellingson, Benjamin M.
Abstract : Purpose: To evaluate a leakage correction algorithm for T 1 and T 2 * artifacts arising from contrast agent extravasation in dynamic susceptibility contrast magnetic resonance imaging (DSC‐MRI) that accounts for bidirectional contrast agent flux and compare relative cerebral blood volume (CBV) estimates and overall survival (OS) stratification from this model to those made with the unidirectional and uncorrected models in patients with recurrent glioblastoma (GBM). Materials and Methods: We determined median rCBV within contrast‐enhancing tumor before and after bevacizumab treatment in patients (75 scans on 1.5T, 19 scans on 3.0T) with recurrent GBM without leakage correction and with application of the unidirectional and bidirectional leakage correction algorithms to determine whether rCBV stratifies OS. Results: Decreased post‐bevacizumab rCBV from baseline using the bidirectional leakage correction algorithm significantly correlated with longer OS (Cox, P = 0.01), whereas rCBV change using the unidirectional model ( P = 0.43) or the uncorrected rCBV values ( P = 0.28) did not. Estimates of rCBV computed with the two leakage correction algorithms differed on average by 14.9%. Conclusion: Accounting for T 1 and T 2 * leakage contamination in DSC‐MRI using a two‐compartment, bidirectional rather than unidirectional exchange model might improve post‐bevacizumab survival stratification in patients with recurrent GBM. J. Magn. Reson. Imaging 2016;44:1229–1237.